The Training of Music Teachers According to Humanistic Oriented Artistic Paradigm - Guralnyk, Nataliia; Zaitseva, Alla; Rastrygina, Alla (Journal of History Culture and Art Research, 2020)
Radical changes in educational policy require the enhancing of educational systems quality and aiming at humanistic values. In this context, problems related to the forming of creative, competitive, existentially free and at the same time responsible citizens of Ukraine, capable of cultural identification and having respect for the “Other’s” culture, get highly actualized. The article addresses the problem of improving the quality of training of specialists in the field of art in higher education, as a derivative of culture, in the context of a humanistic-oriented artistic paradigm. The introduction of the humanistic-oriented paradigm in art education has a dramatically innovative character, focusing future music teachers on the mobility and variability in the selection of forms and methods of artistic communication, and focuses on the subjective position of participants in the interaction with art. The accordance with international educational standards necessitates a holistic approach to the artistic and educational process need to prepare a competitive specialist. The article suggests the methods of theoretical analysis and generalization, which made it possible to formulate the investigated definition, which should be noted that a personality’s culture is characterized not only by the ability for direct dialogue with art but also by “communication on the point of works of art”. The phenomenology of communication in the artistic and educational projection is highlighted and the basic methodological guidelines for the formation are outlined. Particular attention is given on the outlining substantiating of an existential-reflective strategy of artistic and pedagogical communication of subjects of interaction with art in the context of a humanistic-oriented artistic paradigm.